Facile synthesis of Fe3O4 via co-precipitation method: The role of Moringa oleifera in substituting chemical reducing agents - Rizqi A’mal Hibatullah Tabrani; Ganesha Antarnusa; Fazri Firdaus (Next Materials)
Magnetite (Fe3O4) nanoparticles have attracted significant interest as a result of their unique magnetic properties and diverse applications in various fields such as biomedicine, environmental remediation, and sensor technology. Although conventional synthesis methods are effective, they often involve toxic reducing agents that pose environmental risks. In this study, we propose an eco-friendly approach to synthesizing Fe3O4 nanoparticles using Moringa oleifera (MO) extract as a natural reducing agent via the co-precipitation method. The effects of varying MO concentrations on the structural, chemical, morphological, and magnetic characteristics of Fe3O4 nanoparticles were systematically investigated. Characterization techniques, including XRD, FTIR, SEM-EDX, TEM-SAED, and VSM, revealed that the partial substitution of NH4OH with MO extract affected the phase composition, crystallite size, and magnetic properties of the nanoparticles. XRD analysis showed the emergence of a secondary Fe2O3 phase and a reduction in crystallite size from 8.38 nm to 1.17 nm. FTIR spectra revealed shifts in Fe-O vibrational modes and the appearance of new peaks, indicating interactions with functional groups in the MO extract. TEM images indicated a morphological transformation from rod-like to more spherical and homogeneous particles. The average grain size decreased from 11 nm to 9.5 nm. However, at higher MO concentrations, agglomeration was observed, increasing the particle size to 13 nm. The sample synthesized with the MO to NH4OH ratio of 1:3 exhibited a balanced set of properties, including high saturation magnetization (30.99 emu/g) and phase purity, while significantly reducing the requirement for chemical reducing agents, thus supporting the principles of green chemistry.